Distributional preferences explain individual behavior across games and time - Morten Hedegaard; Rudolf Kerschbamer; Daniel Müller; Jean-Robert Tyran (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
We use a large and heterogeneous sample of the Danish population to investigate the importance of distributional preferences for behavior in a public good game and a trust game. We find robust evidence for the significant explanatory power of distributional preferences. In fact, compared to twenty-one covariates, distributional preferences turn out to be the single most important predictor of behavior. Specifically, subjects who reveal benevolence in the domain of advantageous inequality contribute more to the public good and are more likely to pick the trustworthy action in the trust game than other subjects. Since the experiments were spread out more than one year, our results suggest that there is a component of distributional preferences that is stable across games and over time.
Keywords: C72; C91; D64; 330; Distributional preferences; social preferences; Equality-Equivalence Test; representative online experiment; trust game; public goods game; dictator game